2021
DOI: 10.1111/jdv.17222
|View full text |Cite
|
Sign up to set email alerts
|

Dermoscopic features of post kala azar dermal leishmaniasis

Abstract: Eyelash poliosis has been described as an atypical manifestation of metastatic melanoma recurrence in one patient who underwent primitive lesion excision three years before; similarly to our case, the primary melanoma was distant from the area of poliosis. 7 The peculiarity of our case is that eyelash poliosis manifested as first clinical sign of an undiagnosed melanoma, not adjacent to the localization of the whitening in contrast to what reported so far, nor a consequence of medication use.Concluding, we w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 4 publications
1
4
0
Order By: Relevance
“…The presence of the latter finding was confirmed by Swarnkar et al , who observed it in hypopigmented macules, papules and nodules. 71 In line with another report, Swarnkar et al also found yellow-orange structureless areas, thought to correspond to dermal granulomas [ 69 , 71 ].…”
Section: Resultssupporting
confidence: 83%
See 1 more Smart Citation
“…The presence of the latter finding was confirmed by Swarnkar et al , who observed it in hypopigmented macules, papules and nodules. 71 In line with another report, Swarnkar et al also found yellow-orange structureless areas, thought to correspond to dermal granulomas [ 69 , 71 ].…”
Section: Resultssupporting
confidence: 83%
“…Three reports have investigated dermoscopy of post-kalaazar dermal leishmaniasis (PKDL) [69][70][71]. The first description by Jha et al reported erythema and follicular plugs [70].…”
Section: Post-kala-azar Dermal Leishmaniasismentioning
confidence: 99%
“…Post‐kala‐azar dermal leishmaniasis (PKDL) is the cutaneous sequela of visceral leishmaniasis and presents as progressively increasing hypopigmented macules, erythematous papules and nodules, and/or facial erythema 124 . Dermoscopy of PKDL has been infrequently reported.…”
Section: Resultsmentioning
confidence: 99%
“…Thakur et al described the presence of yellow structureless areas with reduced pigment network and preservation of appendages in two patients. 124 The preservation of appendages was highlighted by the authors as a possible clue to help differentiate PKDL from lepromatous leprosy (where a loss of appendages is appreciated). Finally, Jha et al 125 described yellow tears corresponding to follicular plugs with surrounding erythema in their patient.…”
Section: Post-kala-azar Dermal Leishmaniasismentioning
confidence: 99%
See 1 more Smart Citation